Agriculture and Rural Development as a Main Objective of Polish Cooperation and Development Aid for the Republic of Moldova - Sikora-Gaca, Małgorzata (Historia i Polityka, 2021)
Agriculture and development of rural areas are important sectors of Polish-Moldovan cooperation and development aid. Importantly, both of them constitute structural problems, similar to those which faced agriculture in Poland in the 1990s. Through Polish aid and development cooperation, various measures are initiated which increase the competitiveness of Moldovan agricultural production, improve sanitary and phytosanitary conditions, bring technological innovations in agricultural farms, ensure modernization of rural infrastructure, providing support to small and medium-sized entrepreneurs, cooperatives, and agricultural consultants, along with professional activation of the Republic’s residents.